Strategi Pengembangan Sumber Daya Manusia dalam Meningkatkan Kualitas Pelayanan Guest House di Kecamatan Kewapante Kabupaten Sikka - Maria Silvana Mariabel Carcia; Anjeliana Grengan; Yunita Densiana; Plasidius Yulianus Aldiyano (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2026)
The tourism industry's rapid growth has intensified competition in the accommodation sector, making human resource (HR) quality a decisive factor in guest house service excellence. This study examines the competitive HR characteristics of Rumah Tamu Romana in Kewapante District, Sikka Regency, based on direct field observation. Five key indicators were assessed: competence, adaptability to change, innovation and creativity, integrity and work ethics, and communication skills. Results indicate that staff demonstrate adequate operational knowledge and consistent adherence to standard operating procedures. However, gaps remain in digital technology adoption, particularly online booking systems. Adaptability is satisfactory, supported by open internal communication. Innovation potential exists in room decoration and independent problem-solving. Integrity and discipline stand out as the strongest indicators, with high attendance and guest privacy protection. Communication skills are effective for domestic guests, with basic English competency for international visitors. The study recommends structured training programs, innovation forums, mentoring, and institutional partnerships to develop more competitive HR capabilities.